Portrayal of Pornography in Malaysian News Media - Pung, Wun Chiew; Ting, Su Hie (2024)
This study examines how pornography is portrayed in a leading Malaysian newspaper from 2017 to 2024. The objectives are to analyse the prevalence of different frames and investigates how the language reflects societal norms over time. Through content analysis of 24 articles using Goffman’s (1974) Framing Theory, the findings show that while episodic frames still dominate case reporting, thematic frames are increasingly connecting incidents to broader societal trends, indicating a shift toward viewing pornography as a systemic issue. The morality frame remains significant, but there is growing emphasis on public health and safety, and technological challenges and responsibility. The language has also shifted from moralistic terms to a focus on public health and safety, protection of vulnerable groups, and technological accountability, highlighting the challenges of addressing pornography in the digital age. This research demonstrates how Malaysian news media has evolved, recognising that tackling pornography requires coordinated efforts involving legal regulations, protection for vulnerable populations, and stricter online monitoring.